Carcass characteristics of lambs fed levels of spineless cactus as a substitute for Tifton hay - ARAÚJO FILHO, José Teodorico de; LIMA, Hugo Batista; FREGADOLLI, Fábio Luiz; VIEGAS, Júlio; PEREIRA, Kedes Paulo; AMORIM, Philipe Lima de; RIBEIRO, Neila Lidiany (Food Science and Technology, 2025)
The aim of this research was to evaluate the effects of including forage palm in the diet of lambs finished in confinement on carcass characteristics. A total of 24 Santa Ines lambs were used, with an average age of 119 ± 30 days and an average initial weight of 14.64 ± 2.28 kg. All the animals were slaughtered after 89 days in confinement. Four diets were formulated, containing four inclusion levels of Palma Miúda (Nopalea cochenillifera Salm-Dyck): 0, 6.5, 16.63, and 35.10% as a substitute for Tifton-85 (Cynodon dactylon) hay. The design used was randomized blocks. The variables final live weight, hot carcass weight, cold carcass weight, hot carcass yield, cold carcass yield, biological yield, loin eye area, subcutaneous fat thickness, grid rule measurement, carcass compactness index, the weights of the neck, palette, loin, rib and leg cuts, and the yields of the loin and rib cuts, showed increasing linear behavior as the amount of Palma Miúda in the diet increased, but the yields of the neck, palette, and leg cuts decreased linearly. Diets with higher palm inclusion provide carcasses with better subcutaneous fat thickness, loin eye area, and carcass compactness index, while also providing higher weights of commercial cuts and lower yields of palette and leg cuts.